ANALISIS KUALITAS LAYANAN SUPERVISI PBNGAWAS SBKOLAH DAN KEPUASAN GURU SMK DI KABUPATEN GUNUNG KIDUL - , Wiryatun ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study describes the quality of service supervision and vocational teacher satisfaction in Gunungkidul. Measurement of service quality using the 5-dimensional analysis SERQUAL tangible, reliability, responsiveness, assurance and empathy. Measurement of satisfaction using satisfaction index by Tjiptono. Respondents in this study were limited to the 100 respondents with a Master's in Vocational School in Gunungkidul. The samples selected using probability sampling technique of cluster sampling (sampling by region / area. Significant research results on four (4) dimensions namely physical evidence 0.0151, 0.0007 responsiveness, assurance and reliability 0.007 0.0028. As for the dimensions of empathy was not significant t test with a score of 0.44. Satisfaction levels of teachers to supervise service supervisor by 75%, meaning that the performance of the supervisor is not fully in accordance with the expectations of the teachers.